(untitled) (Herald of the National Children’s Medical Center, 2025)
This study analyzes the diagnosis and surgical treatment of spontaneous gastrointestinal perforations (SPC) in newborns to optimize management strategies and improve outcomes. Based on the examination of 52 newborns with perforating peritonitis, including 39 cases of necrotizing enterocolitis (NEC) and 13 cases of SPC, the main risk factors identified were birth asphyxia and respiratory distress syndrome. Surgical treatment included perforation closure in 11 cases and direct anastomoses in 2 cases with larger defects. Mortality was 50% in NEC and 26% in SPC, primarily affecting premature infants with low birth weight and severe comorbidities. Early diagnosis and individualized surgical approaches were key to improving outcomes.